Integrated Outdoor and Indoor Tracking Through GPS, LTE and Wi-Fi Solution - Bee Yan , Seh; Che Seman , Fauziahanim (Evolution of Information, Communication and Computing System, 2022)
Nowadays, the outdoor tracking system that utilizes the GPS signal become a common technology. A GPS Navigator System is a must have gadget to a driver as it helps to navigate driver to any places easily. On the other side, an indoor location is becoming more important to help us navigate especially in a wide building with multi floors spaces. Here, the main challenges is the fact that inside a buildings a GPS signal is not that strong to operate [1]. However, this limitation may be overcome if Wi-fi signal which is commonly available in a closed area and supported by cellular signals can perform similar operation as GPS signal. Cellular signals or to be specific is the Long-Term Evolution (LTE) signal and WI-FI signal can be analyzed to perform estimation for indoor tracking [2]. This chapter explains about the proposed outdoor and indoor tracking system to estimation location of stationary and mobile objects in the open terrain as well as inside a building by utilizing GPS signal, cellular signal and WiFi signal. The accuracy of the system is found within 5 m and 2 m range for outdoor and indoor environment respectively. The estimation of the location is uploaded to cloud based platform, ThingSpeak. In this proposed system, we are utilizing the Motorola board known as M-WiCom platform, act as the key component and able to upload the estimated location in a cloud platform, ThingSpeak. The workability of the system is evaluated by conducting few experiments in UTHM campus area.